KARAKTERISTIK KIMIAWI MIE KERING DENGAN SUBSTITUSI TEPUNG KACANG MERAH (Phaseolus vulgaris L.) DAN EKSTRAK BIT (Beta vulgaris L) DENGAN BERBAGAI PERLAKUAN PENDAHULUAN - AKHMAD MUSTOFA; YANNIE ASRIE WIDANTI (Universitas Riau, 2017)
Noodles is one of the favorite foods in Indonesia. This condition is due to the practicality in processing thenoodles so that anyone does not take long to cook it and can be served in various variations. Therefore itneeds an innovation to make dry noodles with other useful compounds such as antioxidants so that the drynoodle can be more healthful for the consumers. The research was done by factorial completely randomizeddesign experiment, ie pre treatment of red beans and the amount of beet extracts added. The results showedthat the best results was found when using pre treatment boiling for red beans for 90 minutes and the additionof 50% beet extract for making dry noodles. This treatment produced dry noodles with phytic acid of 0.398%,acid number of 0.291 mg KOH / g of oil and antioxidant activity of 42.188%.